In vivo genotoxicity of 2-alkylcyclobutanones in liver cells from rats fed with irradiated cocoa butter using flow citometry. - Regiane Martins; Daniel Perez Vieira; Luma Ramirez de Carvalho; Angélica Bueno Barbezan; Anna Lucia Casañas Haasis Villavicencio (Brazilian Journal of Radiation Sciences)
Food irradiation proves to be an effective technique of eliminating some pathogens from food and this has gained significant attention to its potential for food safety. Since 1990, studies on the toxicological safety of 2-Alkylcyclobutanones have been conducted extensively. 2-Alkylcyclobutanones are unique radiolytic products generated by the radiation-induced breakage  of triglycerides in food, 2-dodecylcyclobutanone (2-dDCB) and 2-tetradecylcyclobutanone (2-tDCB) are the predominant compounds detected . Despite studies showing non-genotoxicity of 2-ACBs (2-Alkylcyclobutanones), the results are conflicting and therefore we continue the studies in order to confirm the compounds  are safety for human health. In vivo micronucleus test were performed to verify the 2-ACBs genotoxic effects in hepatic cells using flow citometry. We used cocoa butter irradiated with 20 kGy. A group with animals  was treated with daily intake of irradiated cocoa butter, synthesized 2-dDCB and 2-tDCB for one month. Hepatic cells were selected for genotoxicity analysis due to the liver importance in the compounds metabolization. The improvement of the analytical techniques is important for the research future since the irradiation process is already consolidated. The results confirmed the safety of the food irradiation process, as they did not indicate the genotoxic potential of the samples.